Effect of Heat and Enzymatic Treatments on Human IgE and Rabbit IgG Sensitivity to White Bean Allergens - Amal Bousfiha; Aarab Lotfi (Iranian Journal of Allergy, Asthma and Immunology, 2013)
The aim of this study was to evaluate the sensitivity of the population of Fez and Casablanca in Morocco to dry white beans (Phaseolus Vulgaris) and to investigate the effect of food processing (heat and/or enzymatic hydrolysis by pepsin) on this sensitivity. Work was based on a bank consisting of 146 sera from patients with atopic hypersensitivity in order to evaluate specific immunoglobulin E (IgE) levels to native and processed white bean proteins by ELISA. Under the same conditions, we assessed the immunoreactivity of rabbit IgG obtained by immunization with native white bean proteins. Evaluation of specific IgE to the white bean proteins showed that 51% of children and 39% of adults had positive values. The heat treatment and pepsin hydrolysis of dry bean proteins showed a reduction of 68% of IgE binding recognition in more than 65% ofall patients. After heating, all patients indicated a reduction greater than 36%. With rabbit IgG, we observed a decrease by 25% of binding under heat treatment while enzymatic digestion reduced IgG recognition by 46.6%. These findings suggest that epitopes recognized by IgE in the studied population were conformational sites whereas those recognized by rabbit IgG were probably sequential. In conclusion, these results demonstrate that the Moroccan population was very sensitive to white  beans  and  this  sensitivity  could  be  reduced  after  heat  treatment  or  enzymatic hydrolysis.